Aspergillus Utilizes Extracellular Heme as an Iron Source During Invasive Pneumonia, Driving Infection Severity. (10th March 2022) - Michels, Kathryn; Solomon, Angelica L; Scindia, Yogesh; Sordo Vieira, Luis; Goddard, Yana; Whitten, Spencer; Vaulont, Sophie; Burdick, Marie D; Atkinson, Carl; Laubenbacher, Reinhard; Mehrad, Borna
Abstract: Background: Depriving microbes of iron is critical to host defense. Hemeproteins, the largest source of iron within vertebrates, are abundant in infected tissues in aspergillosis due to hemorrhage, but Aspergillus species have been thought to lack heme import mechanisms. We hypothesized that heme provides iron to Aspergillus during invasive pneumonia, thereby worsening the outcomes of the infection. Methods: We assessed the effect of heme on fungal phenotype in various in vitro conditions and in a neutropenic mouse model of invasive pulmonary aspergillosis. Results: In mice with neutropenic invasive aspergillosis, we found a progressive and compartmentalized increase in lung heme iron. Fungal cells cultured under low iron conditions took up heme, resulting in increased fungal iron content, resolution of iron starvation, increased conidiation, and enhanced resistance to oxidative stress. Intrapulmonary administration of heme to mice with neutropenic invasive aspergillosis resulted in markedly increased lung fungal burden, lung injury, and mortality, whereas administration of heme analogs or heme with killed Aspergillus did not. Finally, infection caused by fungal germlings cultured in the presence of heme resulted in a more severe infection. Conclusions: Invasive aspergillosis induces local hemolysis in infected tissues, thereby supplying heme iron to the fungus, leading to lethal infection. Abstract : We report that invasive aspergillosis results in localized hemorrhage and heme release in infected tissues. The fungus then takes up heme from the environment, thus acquiring the essential element, iron. This renders the organism more virulent during in vivo infection.